The Reality of Electronic Banking in Algeria: A Case Study of the (BNA) - laadjal, lamria (Journal of Research in Finance and Accounting, 2025)
The study aims to analyze and evaluate the application of electronic banking in the National Bank of Algeria (BNA), through a case study of this bank, analyzing the extent of the use of technology in providing banking services, and analyzing the extent of its impact on customers and the general performance of the bank. The results of the study indicate that electronic banking at the National Bank of Algeria is considered advanced, as it provides a wide range of banking services via the Internet and mobile phones, as well as easy-to-use applications. However, security challenges around the use of electronic banking remain important to ensure the continuity of these services.